2007
DOI: 10.1007/s00535-007-2112-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of basement membrane type IV collagen α chains in gastric intramucosal neoplastic lesions

Abstract: The loss of alpha5/alpha6(IV) chains might be a useful diagnostic finding for gastric intramucosal carcinoma in GINL cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
(34 reference statements)
3
12
0
Order By: Relevance
“…Similarly, we found that TGF-β1 stimulation, in a dose-dependent manner, increased the production and mRNA expression of α1(IV) and α2(IV) chains, but not α3(IV) to α6(IV) chains, by cultured human lung fibroblasts. Consistent with our data are findings that α3 (IV) to α6(IV) chains tended to disappear in acinar and ductal BMs of the labial salivary gland in Sjögren's syndrome 33 and in the BM of several malignant neoplasms, such as bronchioloalveolar carcinoma 18 and gastric carcinoma, 34 but that α1(IV) and α2(IV) chains were expressed continuously in the BM even in those pathologic conditions. Moreover, no reliable report about α3(IV) to α6(IV) chains being produced by cultured fibroblasts in vitro has been published.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, we found that TGF-β1 stimulation, in a dose-dependent manner, increased the production and mRNA expression of α1(IV) and α2(IV) chains, but not α3(IV) to α6(IV) chains, by cultured human lung fibroblasts. Consistent with our data are findings that α3 (IV) to α6(IV) chains tended to disappear in acinar and ductal BMs of the labial salivary gland in Sjögren's syndrome 33 and in the BM of several malignant neoplasms, such as bronchioloalveolar carcinoma 18 and gastric carcinoma, 34 but that α1(IV) and α2(IV) chains were expressed continuously in the BM even in those pathologic conditions. Moreover, no reliable report about α3(IV) to α6(IV) chains being produced by cultured fibroblasts in vitro has been published.…”
Section: Discussionsupporting
confidence: 91%
“…In this connection, other investigations have focused on the expression of ECM components in the stomach and their role in pathological gastric conditions (Gillensen et al 1993, Shahin et al 1997, Baba et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…All six type IV collagen α-chains have been identified in the human colon by immunofluorescence staining using chain-specific monoclonal antibodies [7]. Invasive growth is a hallmark of malignancy in cancers and several studies suggest that the loss of tissue specific α(IV) chains in the epithelial BM may be related to biologically significant events in the invasive stage of cancer in different tissues [8-17]. …”
Section: Introductionmentioning
confidence: 99%